Penerapan Teknologi Fermentasi Probio_FM pada Pakan Berbasis Ikan Rucah untuk Mendukung Kemandirian Pakan Mitra Cafetaria Sehat Kuala Tungkal - Fahmida Fahmida; Darlis Darlis; Anie Insulistyowati; Pudji Rahayu; Wulandari Wulandari; Nurhayati Nurhayati; Eka Sri Wahyuni (PELITA NUSA TENGGARA, 2026)
Feed is the main problem faced by Cafetaria Sehat farmers due to its relatively high cost. This community service program aims to produce an alternative feed through the formulation of pellets made from trash fish supplemented with the Probio_FM probiotic, intended to improve nutritional quality and reduce production costs. The program was carried out through five stages: observation, socialization, pellet-making training, laboratory testing and field application, and monitoring. Laboratory analysis showed that the three types of pellets produced contained high protein levels (22.80–24.59%), although fiber content remained above the SNI standards. Application of the fermented feed to ULU native chickens resulted in good growth performance, with harvesting at 58 days and a low mortality rate of 0.5%. In Sangkuriang catfish, the feed produced positive responses, indicated by good consumption rates and harvest size of 6–7 fish/kg at 62 days. The use of Probio_FM is presumed to enhance digestive efficiency, gut microbiota balance, and overall growth performance. This program successfully improved partners’ knowledge and skills in producing self-formulated feed using trash fish, thereby reducing dependence on commercial feed. Overall, the fermented trash-fish-based feed technology with Probio_FM is effective, economical, and has strong potential for sustainable application in community-based livestock and aquaculture enterprises.